PENGARUH PARTISIPASI PENGANGGARAN PADA SENJANGAN ANGGARAN DENGAN KARAKTER PERSONAL PESIMIS SEBAGAI VARIABEL PEMODERASI - Ernayanti, Ni Putu; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi, 2017)
The purpose of this research is to see the effect of budgetary participation on budgetary slack, personal character pessimistic influence on budgetary slack and personal character pessimistic view as a moderating influence on budgetary slack budgetary participation. Variable personal character pessimistic in this study acts as the independent variable and the moderating variable. The research was conducted on 44 SKPD in Klungkung and used three respondents for each SKPD. In this study, the data used is primary data collected from 132 respondents through questionnaires distributed directly by using purposive sampling technique. This study used Moderated Regression Analysis (MRA) as data analysis techniques. These results indicate that the participation budgeting positive influence on budgetary slack. Personal character pessimistic positive effect on anggran slack. Personal character pessimistic moderate (weaken) the effect of budgetary participation on budgetary slack.
Keywords: Participation Budgeting, Personal Character Pessimists, Budgetary Slack